2019
DOI: 10.1111/hsc.12781
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion for mild frailty based on behaviour change: Perceptions of older people and service providers

Abstract: Mild frailty is common among older people, but it is potentially reversible with health promotion interventions. Behaviour change may be a key to preventing progression of frailty; however, we know little about what interventions work best and how a behaviour change approach would be perceived by this group. The aim of this study was to explore how mildly frail older people perceive health promotion based on behaviour change and what factors affect engagement with this approach. We conducted semi‐structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…Regarding the measurement of frailty, five articles used the Clinical Frailty Scale 11,15,[22][23][24] , four used the Frailty Phenotype 14,23,25,26 , three used the Tilburg Frailty Indicator [27][28][29] , two used the Comprehensive Frailty Assessment Instrument 10.30 , five defined frailty without an instrument or objective measurement 4.14. [31][32][33] , one article used Prisma-7 6 and one the Edmonton Frailty Scale 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the measurement of frailty, five articles used the Clinical Frailty Scale 11,15,[22][23][24] , four used the Frailty Phenotype 14,23,25,26 , three used the Tilburg Frailty Indicator [27][28][29] , two used the Comprehensive Frailty Assessment Instrument 10.30 , five defined frailty without an instrument or objective measurement 4.14. [31][32][33] , one article used Prisma-7 6 and one the Edmonton Frailty Scale 34 .…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] , one article used Prisma-7 6 and one the Edmonton Frailty Scale 34 . Of these, in two articles 14,23 there was the combination of more than one instrument. In nine articles, the measurement of frailty was not explicit 18.35-42 .…”
Section: Resultsmentioning
confidence: 99%
“…The WE-RISE at Home program strongly promotes the continuation of self-management following the instructed sessions at the comforts of their own home. The elements of social engagement via phone call with instructor, autonomy to select the activities of choice at home and setting targets to achieve for each session are promising components that heighten motivation to carry out activities independently (65). The WE-RISE intervention hopes to provide easier accessibility whilst enabling "age-friendly" health care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) points out that being person‐centred requires establishing a person‐centred culture and working with the beliefs and values of patients as well as shared decision making. One study found that health professionals experienced that it was difficult for some frail older people to identify goals that they would find motivational and relevant, and also how much they wanted professionals to push them towards achieving these goals (Avgerinou et al., 2019). With regard to nutritional goals, other studies found that staff need to communicate with patients and their carers about their usual eating habits and be sensitive to the patients’ wishes, in order to be able to assess the patients’ motivation to eat (Chapman et al., 2015; Soderhamn & Soderhamn, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A focused literature search in PubMed, CINAHL and Embase on the perspectives of health professionals on frailty in general, and specifically on physical activity, identified studies that showed that health professionals view a number of factors as important in care or interventions for frail older people. Among these are: establishing a relationship between patient and professional (Avgerinou et al., 2019; Bindels, Cox, Widdershoven, van Schayck, & Abma, 2014; Frost et al., 2018; Gwyther et al., 2018; Lette, Baan, Van Den Berg, & De Bruin, 2015); and having a person‐centred approach or tailoring interventions to individual needs (D'Avanzo et al., 2017; Frost et al., 2018; Giguere et al., 2018; Lette et al., 2017; Shaw et al., 2017). Moreover, organisational factors such as poor communication or lack of co‐ordination and collaboration can create difficulties (Giguere et al., 2018; Gwyther et al., 2018; Lette et al, 2015; Sadler et al., 2019).…”
Section: Introductionmentioning
confidence: 99%